OPTIMASI LAHAN DENGAN SISTEM TUMPANG SARI JAGUNG MANIS (Zea mays saccharata, Sturt) DAN KANGKUNG SUTRA (Ipomea reptans) DI PEKANBARU - Surtinah Surtinah; Neng Susi; Sri Utami Lestari (Jurnal Ilmiah Pertanian, 2016)
Research conducted experiments using a completely randomized design environment with three replications, and design of treatment that is the time of planting silk kale as secondary crops to the cultivation of sweet corn (K) consisting of: k1 = planting at the same time; k2 = time of planting silk kale 1 week after planting sweet corn; k3 = time of planting silk kale 2 weeks after planting sweet corn; k4 = time of planting silk kale 3 weeks after planting sweet corn; K5 = single planting sweet corn planting time = k1; k6 = single silk kale planting time = k1. The results showed that silk kale can be planted together with sweet corn planting time, up to three weeks after planting sweet corn. Results of sweet corn is not influenced by the timing of planting different silk kale. Land values in the cropping system Equality sweet corn with silk kale is 1.83. Competition index between sweet corn and silk kale is 1.73.